Monte Carlo dosimetric characterization of the IRAsource high dose rate Iridium-192 brachytherapy source: Comparison with the mHDR-v2r model - Shuhei Tsuji (PLoS ONE, 2026)
The aim of this study was to evaluate the dosimetric characteristics of an IRAsource brachytherapy source using Monte Carlo simulations incorporating source electron effects. The dose rate constant, radial dose function, and two-dimensional (2D) anisotropy function were calculated and compared with those of published data and results of the mHDR-v2r source model. The dose rate constant obtained for the IRAsource was ( 1.1142 ± 0.0030 ) c G y h − 1 U − 1 , which was consistent with previously reported values, within the range of experimental uncertainty. The radial dose function exhibited a pattern similar to that of the mHDR-v2r source, with dose distributions converging at distances of approximately 10 cm, where the effect of capsule thickness became negligible. The 2D anisotropy function did not fully align with other experimental datasets for the IRAsource. Even when comparing the IRAsource with mHDR-v2r sources, the 2D anithotropy function showed a difference of 3% to 6% around 0 degrees at distances of 0.25 cm to 5.0 cm from the source. The results reflected reasonable trends that were consistent with differences in source capsule geometry of the IRAsource and the mHDR-v2r. These findings show that the dosimetric data presented here is reliable. This study provides essential baseline data for accurate dose assessment of the IRAsource in brachytherapy and underscores the importance of further experimental validation to refine dose characterization.